Assessment of Carcinogenic and non-carcinogenic risk indices of heavy metal exposure in different age groups using Monte Carlo Simulation Approach - Shetty, B Raksha; Pai, B Jagadeesha; Salmataj, S A; Naik, Nithesh (Scientific reports, 2024)
Dermal contact, ingestion and inhalation of heavy metal poses significant health risk in human subjects. The exposure could be via potable water, soil or air. The current experiment design focuses on soil media and exposure. Advanced probabilistic and geospatial methods are used in this study which evaluates contamination levels and health risks associated with iron (Fe), arsenic (As), zinc (Zn), copper (Cu), nickel (Ni), chromium (Cr), lead (Pb), and cadmium (Cd) in soil samples. The samples were collected and analysed using ICP-OES after tri-acid digestion, and indices such as Geoaccumulation Index (Igeo), Contamination Factor (CF), Pollution Load Index (PLI), Hazard Quotient (HQ), Hazard Index (HI), and Carcinogenic Risk (CR) were used to assess environmental impacts and health risks across the age groups via oral ingestion, inhalation and dermal contact. The current study indicates heavy metal concentrations follow the order Ni > Zn > Pb > Cu > Cr > As > Cd, with more than 60% of samples demonstrating significant pollution levels. The computational method used in the study revealed substantial non carcinogenic risk (HQ > 1) and carcinogenic risk (33%) in the population related to As exposure. Geospatial analysis and Monte Carlo simulations helped in identifying the hotspots in the tropical coastal area emphasizing need for targeted remediation focusing on As and Pb.